Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
Easy answer
Its 0
I hope it's correct Good luck...
Yes it is. log(1) and ln(1) both equal zero. But you cannot take the logarithm of 0.
The answer is D). A perfect square
b2 - 4ac > 0
Roots are real, unequal and rational.
Answer:
-11.7 is the correct answer. Hope this helps
The complete question in the attached figure
we have that
f(x) = x²<span> + 1
g(x) = x – 4
step 1
find </span>(f o g)(x)
(f o g)(x)= (x - 4)² + 1(f o g)(x) = x² - 8x + 16 + 1
(f o g)(x) = x² - 8x + 17
step 2
find (f o g)(10)
(f o g)(10) = 10² - 8*(10) + 17
(f o g)(10 = 100 - 80 + 17
(f o g)(10)= 37
the answer is 37